The use of formaldehyde protected palm kernel meal and its effects on animal performance, nitrogen utilization and unsaturated fatty acid composition in Priangan sheep - K.G Wiryawan; A Parakkasi; R Priyanto; I.P Nanda (Indonesian Center for Animal Research and Development (ICARD), 2007)
An experiment was conducted to investigate the effect of formaldehyde-treated Palm Kernel Cake (BIS) in male Priangan sheep diet and its effect on animal performance, N utilization, and unsaturated fatty acids composition of musculus longisimus dorsal. The experiment was designed based on completly randomized design with four treatments and nine replications. The treatments consisted of four levels of formaldehyde treated BIS: R1 (0%), R2 (15%), R3 (30%) and R4 (45%). Results indicated that formaldehyde treated BIS up to 45% in diet did not negatively affect consumption, dry matter digestibility and daily live weight gain. Formaldehyde protection especially in R4 could significantly reduce ruminal N-NH3 concentration, increased protein digestibility and nitrogen retention, but did not influence allantoin urine concentration. Unsaturated fatty acid composition of musculus longisimus dorsal was not affected by formaldehyde treated BIS in diet. It is concluded that the inclusion of 45% formaldehyde treated BIS in diet did not negatively affect animal performance, and R4 is the most effective in improving nitrogen utilization in male Priangan sheep, but unable to alter the unsaturated fatty acids composition of musculus longisimus dorsal. Key Words: Palm Kernel Cake, Formaldehyde, Performance, Nitrogen, Unsaturated Fatty Acids